IMPLEMENTATION OF INQUIRY-BASED DIFFERENTIATED LEARNING IN IMPROVING STUDENTS' CRITICAL THINKING SKILLS - Ramdani, Nurlailatun; Nurwalidainismawati, Nurwalidainismawati; Fauzi, Azra (FKIP Universitas Muhammadiyah Tangerang, 2025)
The development of critical thinking skills is one of the learning objectives applied in the Merdeka Curriculum through the Pancasila student profile. However, the implementation of the Merdeka Curriculum that meets the students' needs has not been fully developed in each school. Therefore, one effort that can be used to address this issue is by implementing differentiated learning based on inquiry learning. This research aims to determine the effect of implementing differentiated learning based on inquiry learning on improving students' critical thinking skills. The research design uses a mixed methods approach. The population in this study includes all 10th-grade students (Class X.E) at SMA Negeri 2 Woha. Using cluster random sampling, two classes were selected as the research sample, with each class consisting of 23 students, divided into an experimental group and a control group. Data collection techniques include test sheets and interviews. Quantitative data analysis was obtained from the test results using the N-Gain and Wilcoxon tests, while qualitative data analysis was obtained from the interview results. The findings show that in the experimental class, 26,2% of students achieved the highest improvement in critical thinking skills, whereas in the control class, 34,8% of students did not experience any improvement in critical thinking skills. In conclusion, there was an improvement in both critical thinking skills and mathematics learning outcomes as a result of implementing differentiated learning based on inquiry learning in the experimental class compared to the control class.